Completing your EdD : the essential guide to the doctor of education - Roffey-Barentsen, Jodi; Reilly, Iona Burnell (Emerald Publishing Limited, 2025)
Undertaking a Professional Doctorate in Education (EdD) can be a daunting yet career-defining task. Through engaging with research, increasing your networks, and conducting your own research project, you will advance your professional practice and understanding of your field. Completing your EdD is the new essential text to guide you through your doctorate. It provides a thorough and comprehensive guide intended to accompany you as you successfully progress through your EdD. It is packed with critical information covering key topics from both the taught modules you will undertake and advice for conducting your own research project. Coverage includes writing at doctoral level, conducting a literature review, theoretical frameworks, research ethics, the relationship with your supervisor, and more. Bridging theory and practice, chapters include practical, real-life examples taken from EdD students' experiences and work, as well as extracts offered by practitioners. Written by current EdD teachers, programme leaders and supervisors, and featuring feedback from recently completed EdD students, this vital resource is a must-read for any EdD candidate and will remain a go-to guide for qualified professionals working in education and beyond.
Includes index.
Keywords: Doctor of education degree.; Education -- Schools -- Levels -- Higher.; Higher education, tertiary education.; elektronické knihy; electronic books